Contribution of Doñana wetlands to carbon sequestration. - Edward P Morris (PLoS ONE, 2013)
Inland and transitional aquatic systems play an important role in global carbon (C) cycling. Yet, the C dynamics of wetlands and floodplains are poorly defined and field data is scarce. Air-water CO2 fluxes in the wetlands of Doñana Natural Area (SW Spain) were examined by measuring alkalinity, pH and other physiochemical parameters in a range of water bodies during 2010-2011. Areal fluxes were calculated and, using remote sensing, an estimate of the contribution of aquatic habitats to gaseous CO2 transport was derived. Semi-permanent ponds adjacent to the large Guadalquivir estuary acted as mild sinks, whilst temporal wetlands were strong sources of CO2 (-0.8 and 36.3 mmol(CO2) m(-2) d(-1)). Fluxes in semi-permanent streams and ponds changed seasonally; acting as sources in spring-winter and mild sinks in autumn (16.7 and -1.2 mmol(CO2) m(-2) d(-1)). Overall, Doñana's water bodies were a net annual source of CO2 (5.2 mol(C) m(-2) y(-1). Up-scaling clarified the overwhelming contribution of seasonal flooding and allochthonous organic matter inputs in determining regional air-water gaseous CO2 transport (13.1 Gg(C) y(-1)). Nevertheless, this estimate is about 6 times < local marsh net primary production, suggesting the system acts as an annual net CO2 sink. Initial indications suggest longer hydroperiods may favour autochthonous C capture by phytoplankton. Direct anthropogenic impacts have reduced the hydroperiod in Doñana and this maybe exacerbated by climate change (less rainfall and more evaporation), suggesting potential for the modification of C sequestration.